Nanoparticle-Delivered Transforming Growth Factor-β1 siRNA Induces PD-1 against Gastric Cancer by Transforming the Phenotype of the Tumor Immune Microenvironment - Fenglei Wu; Xiujuan Xu; Wei Li; Yidong Hong; Huan Lai; Jingzhou Zhang; Xueyu Wu; Kangjie Zhou; Nan Hu (MDPI AG, 2022)
Immune checkpoint blockade (ICB) is currently considered to be an important therapeutic method, which obtained FDA approval for clinical use in gastric cancer in 2017. As a new mechanism, it was found that the effect of αPDL1 could be improved by blocking the TGF-β1 signaling pathway, which converts the tumor immune microenvironment from the "immune-excluded phenotype" to the "immune-inflamed phenotype". Based on this phenomenon, this project was designed to prepare TGF-β1-siRNA-loaded PEG-PCL nanoparticles conjugated to αPDL1 (siTGF-β1-αPDL1-PEG-PCL) since we have linked similar antibodies to PEG-PCL previously. Therefore, MFC tumor-engrafted mice were established to simulate the biological characteristics of converting the phenotype of the immune microenvironment, and to study the anti-tumor effect and possible molecular mechanism. In this study, αPDL1 antibody conjugates markedly increased the cell uptake of NPs. The produced αPDL1-PEG-PCL NPs efficiently reduced the amounts of TGF-β1 mRNA in MFC cells, converting the immune microenvironment of MFC tumors engrafted mice from the "immune-excluded phenotype" to the "immune-inflamed phenotype". PDL1-harboring gastric cancer had increased susceptibility to αPDL1. The value of this drug-controlled release system targeting the tumor microenvironment in immune checkpoint therapy of gastric cancer would provide a scientific basis for clinically applying nucleic acid drugs.